2023
DOI: 10.1039/d3nj00247k
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the activity of single atom catalysts for CO2 reduction to C2 products: A high throughput computational screening

Abstract: Tunable electronic structure of the central metal atoms in single-atom catalysts (SACs) helps to control the adsorption energy of reactants and different reaction intermediates involved in multistep chemical processes. Although...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…54,55 This methodology has been employed to study CO 2 hydrogenation reactions on the surface of heterogeneous catalysts. 10,42,44,56 The combined experimental and computational investigation of the CO 2 to methanol on sulfur vacancyrich MoS 2 demonstrated by Deng and coworkers using a similar DFT method validates the reliability of the DFT methods employed in this study. 10 The surface of the orthorhombic model of Fe 2 C was built in a 2 × 2 × 2 supercell.…”
Section: ■ Computational Detailssupporting
confidence: 77%
See 1 more Smart Citation
“…54,55 This methodology has been employed to study CO 2 hydrogenation reactions on the surface of heterogeneous catalysts. 10,42,44,56 The combined experimental and computational investigation of the CO 2 to methanol on sulfur vacancyrich MoS 2 demonstrated by Deng and coworkers using a similar DFT method validates the reliability of the DFT methods employed in this study. 10 The surface of the orthorhombic model of Fe 2 C was built in a 2 × 2 × 2 supercell.…”
Section: ■ Computational Detailssupporting
confidence: 77%
“…The periodic density functional calculations were performed using the Vienna Ab initio Simulation Package (VASP) , to get fundamental insight into the CO 2 hydrogenation pathway on the Fe 2 C catalyst surface. The projector augmented-wave pseudopotential method with the Perdew–Burke–Ernzerhof exchange-correlation functional and a plane-wave cutoff energy of 600 eV was adopted. , Grimme’s zero-damping DFT-D3 method was used to calculate the van der Waals correction. , This methodology has been employed to study CO 2 hydrogenation reactions on the surface of heterogeneous catalysts. ,,, The combined experimental and computational investigation of the CO 2 to methanol on sulfur vacancy-rich MoS 2 demonstrated by Deng and coworkers using a similar DFT method validates the reliability of the DFT methods employed in this study . The surface of the orthorhombic model of Fe 2 C was built in a 2 × 2 × 2 supercell.…”
Section: Computational Detailsmentioning
confidence: 99%
“…S33–S35, ESI‡). 14,16,20,22,69–71 In brief, the EXAFS study suggested a hexa-coordinated environment around Co 2+ , coordinated with two water molecules (axial positions), two chloride ions and two nitrogen atoms of the COF framework (Fig. 3(d)).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, upon proton-coupled reduction of [Co II (η 2 -COF-N,N′)(CH 3 )(CO)Cl 2 ] ( OC*CH 3 ), a rapid C–C coupling is likely to be occurred to generate C 2 -intermediate [Co II (η 2 -COF-N,N′)(OCHCH 3 )Cl 2 ] ( *OCHCH 3 ) (Δ G = −1.48 eV). 69,70 In the next step, proton-coupled reduction of [Co II (η 2 -COF-N,N′)(OCHCH 3 )Cl 2 ] ( *OCHCH 3 ) would afford [Co II (η 2 -COF-N,N′)(OCH 2 CH 3 )Cl 2 ] ( *OCH 2 CH 3 ) (Δ G = +0.45 eV), which upon further proton-coupled reduction resulted in the formation of [Co II (η 2 -COF-N,N′)(HOCH 2 CH 3 )Cl 2 ] ( *HOCH 2 CH 3 ) (Δ G = −2.04 eV). Finally, the intermediate [Co II (η 2 -COF-N,N′)(HOCH 2 CH 3 )Cl 2 ] ( *HOCH 2 CH 3 ) expected to release ethanol (Δ G = +0.03 eV) and the initial catalyst [Co II (η 2 -COF-N,N′)(H 2 O) 2 Cl 2 ] ( H 2 O*OH 2 ) would be regenerated by retaking two water molecules, which would then re-enter into the catalytic cycle to continue the ethanol production (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other scholars came to similar results that were well-researched. 20,21 In addition, SACs exhibited good activity for electrochemical N 2 reduction, 22 CO 2 reduction, 23–25 lithium–sulfur batteries, 26 NO electroreduction 27,28 and CO detection. 29 Thus, the study on axial heteroatom-decorated Fe SAC for ORR is important, and this paper can shed light on the rational design of SAC catalysts with good performance.…”
Section: Introductionmentioning
confidence: 98%